Control of DFIG Wind Turbines Based on Indirect Matrix Converters in Short Circuit Mode to Improve the LVRT Capability. (12th December 2013) - Khajeh, Ahmad; Ghazi, Reza
Abstract : Nowadays, the doubly-fed induction generators (DFIGs) based wind turbines (WTs) are the dominant type of WTs. Traditionally, the back-to-back converters are used to excite the rotor circuit of DFIG. In this paper, an indirect matrix converter (IMC) is proposed to control the generator. Compared with back-to-back converters, IMCs have numerous advantages such as higher level of robustness, reliability, and reduced size and weight due to the absence of bulky electrolytic capacitor. According to the recent grid codes wind turbines must have low voltage ride-through (LVRT) capability. In this paper a new crowbar system is proposed so that along with the control system it protects the IMC from large fault currents and supports the grid voltage dips during grid faults. This crowbar system is provided using the existing converter switches to establish a short circuit mode without any extra circuitry. Even in severe fault conditions, the duration of short circuit mode is quite small so the control system will be activated shortly after the fault to inject reactive power as required by new LVRT standards. Therefore, the new LVRT standards are well satisfied without any extra costs. PSIM simulation results confirm the efficiency of the proposed method.